Dog demography and ecology with reference to rabies in the Amhara region, Ethiopia - Liuel Yizengaw Adnie; Wudu Temesgen Jemberu; Adane Bahiru Woreta; Adugna Berju; Araya Mengistu; Zeleke Tesema Wondie; Wassie Molla; Sefinew Alemu Mekonnen (Heliyon)
Knowledge of domestic dog ecology and demography has been recognized as central to the design of an effective rabies control program. The study was conducted to assess owned dogs' ecology and demography and to identify predictors associated with dog ownership and rabies occurrence in the Amhara region, Ethiopia. Method: ology: The study employed dog census and questionnaire surveys of 907 households selected using a multistage sampling technique from six rural and six urban districts of the Amhara region, Ethiopia. The ecology and demography of owned dogs in the selected areas were recorded and described using descriptive statistics. Mixed-effect logistic regression models were used to identify factors associated with dog ownership and rabies occurrence. Results: A total of 6609 dogs were estimated from 42 kebeles in the 12 study districts. The male-to-female ratio of dogs was 1.7:1.0, and the mean age of dogs was 3.2 years. The proportion of households who owned at least one dog was 5.9 %. The average number of dogs per dog-owned household was 1.3. Dog to household ratio was 1.0:13.0, and dog to human ratio was 1.0:48.5. The majority of the dog owners (97 %) keep dogs for home guard and livestock herding. Only 57 % of the dogs were confined, and 16 % of them were vaccinated. Ninety-one percent of the dog owners did not practice neutering and spaying for dog population control. Religion, livestock ownership pattern, and occupation were associated with dog ownership (p < 0.05). Community residence and age of respondents were associated with rabies occurrence (p < 0.05), while zone was associated with both dog ownership and rabies occurrence at p-value <0.05. Conclusions: The study indicated a low dog population relative to humans, which might make dog-based rabies control manageable. But at the same time, most dogs were not properly managed (confined and vaccinated), which calls for more awareness about responsible dog ownership to reduce zoonotic disease risk, including rabies. Generally, the study provides useful information about the demography and ecology of owned dogs in relation to rabies for making proper and effective rabies control strategies and is important to design the spatial distribution of rabies vaccination in dogs. However, as the study did not include stray dogs, which have great contributions to the spread of rabies, the information should be used with this caveat into consideration.